Reflection on the Contribution of Environmental Development and Energy Resilience from Bengkulu to Indonesia - Oktoyoki, Hefri; Safnizar, Safnizar; Ansiska, Paisal (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Bengkulu's resources hold potential for Indonesia's future. This research, using a qualitative method through literature review, aims to create an in-depth report. The social forestry program in Bengkulu contributes to reducing emissions and poverty. The region's marine biodiversity includes fish, mangroves, and coral reefs. Erosion and accretion occur at river mouths due to waves and construction. The community is aware of socio-economic vulnerabilities. A proposed coastal management strategy involves coastal cell units. The expansion of mangrove areas has been claimed by various parties. The mangrove ecosystems in Bengkulu exhibit specific temperatures, salinity, pH, DO, and TDS levels. Conservation efforts involve local communities. Bengkulu also has potential for hydropower in Lebong, North Bengkulu, Kaur, and Muko-Muko. Additionally, Bengkulu's energy potential includes geothermal and micro-hydro power. Strategic utilization is needed for long-term energy security. New applications of these resources have positive impacts on villages, energy efficiency, and economic opportunities. A map of micro-hydro energy potential is essential for its benefits, and Bengkulu is crucial for national energy security.